1994
DOI: 10.1248/bpb.17.1645
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Level of Urinary Thiobarbituric Acid Reactant in Healthy Humans under Different Physiological Conditions.

Abstract: The level of urinary thiobarbituric acid (TBA) reactants in healthy human subjects due to malonaldehyde derivatives was measured to assess the lipid peroxidation status of the whole body. For each subject the TBA reactant level over a day varied over a 2-3 fold range while the daily level varied over a 1.5-3 fold range under normal life-style conditions. One of the factors causing an increase in the reactant level within a single day may be the subjects's physical activity, because the reactant level of each s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 1 publication
1
25
0
Order By: Relevance
“…In agreement with this suggestion, in healthy subjects, remaining awake all night was responsible for an important increase in urine level of thiobarbituric acid-reactive substances, which are a known indicator of lipid peroxidation (37). Other experimental studies have demonstrated that psychologic stress decreases DNA repair (38) and inhibits radiation-induced apoptosis (39) in human blood leukocytes.…”
Section: Discussionsupporting
confidence: 57%
“…In agreement with this suggestion, in healthy subjects, remaining awake all night was responsible for an important increase in urine level of thiobarbituric acid-reactive substances, which are a known indicator of lipid peroxidation (37). Other experimental studies have demonstrated that psychologic stress decreases DNA repair (38) and inhibits radiation-induced apoptosis (39) in human blood leukocytes.…”
Section: Discussionsupporting
confidence: 57%
“…Emotionally stressed rats have increased levels of 8-deoxy-hydroxy-guanosine (8-OhdG), a commonly used biomarker of oxidative stress (57). Similarly, staying awake all night increased the levels of thiobarbituric acid reactive substances (an indicator of lipid peroxidation) in humans (58). It is plausible that chronic stress may enhance airway inflammation through similar mechanisms to influence lung function.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the blood MDA concentration is not regarded as a very precise parameter. Since lipid peroxidation products measured in excreted urine most probably indicate the total oxidative status of the whole body [22,23], the measurement of a 24-hour rate of MDA urine excretion is generally considered much more accurate than measurement of the MDA blood concentration. Additionally, the study by Yang et al [4] measured the serum MDA concentration.…”
Section: Discussionmentioning
confidence: 99%